Analisis Perhitungan Harga Pokok Produksi Dan Kelayakan Usaha Sedotan Prupuk (Phragmites karka (Retz) Trin ex Steud) Di Desa Tumbang Nusa, Pulang Pisau - Arief R. Hakim; Asro L. Indrayanti; Novita Chandrawijaya (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Communities in Tumbang Nusa Village, Jabiren Raya District Pulang Pisau Regency began to develop prupuk (Phragmites karka (Retz) Trin ex Steud) as a straw material to replace plastik that is difficult to decompose. This study aims to calculate the cost of production, develop a selling price scenario and conduct a feasibility study on the development of straws from prupuk. Primary data was collected from 20 people involved in making pru[uk straws and supplemented with secondary data from various previous studies and publications.The results of this study indicate that the cost of production of prupuk straws ranges between IDR 374.3 - IDR 408.68 per pcs. The proportion of prupuk straw financing is for the purchase of raw materials (59.72% to 65.14%), labor costs (34.36% to 39.58%) and overhead costs for capital financing (0.6% to 0.7 %). Determination of the selling price is done by adding the cost of goods manufactured to the desired profit (mark up method) with scenario I with a profit rate of 10% (amounting to IDR 389.04 for large packages and IDR 449.54 for small packages) to scenario VI with a level of 60% profit (IDR 565.88 for large packages and IDR 653.88 for small packages). In terms of price, determining the selling price up to scenario VI can still compete with the prices of its competitors, namely bamboo straws. Although the price of the product is competitive, the level of labor productivity is very low. At the break even point condition, the maximum labor income is only IDR 180,062.74. When compared with the UMR District of Pulang Pisau, the income contribution received from making this purun straw is very small (only 6.11%). In order to achieve an income level equivalent to the UMR of Pulang Pisau Regency, a production turnover of 383 pcs per person per day is needed or equal to 7,652 pcs per person per month. In order to improve the quality and quantity of prupuk straws, it is necessary to apply production technology.